Pengembangan Kerangka Manajemen Risiko pada Perbankan Syariah - Novianti, Diah (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2019)
Islamic banking such as the other business institution will face different kind of risk that inherent on its main business activity. In business, risk defined as a posibillity an can appear every time, before, when, and after the decision making. Islamic banking faced different risk with the conventional banking, because its uniquenes. Thus, the development of risk management framework in Islamic banking is very important to do, especially in frame of risk identification, measuring, mitigation and monitoring. This paper will discuss about risk management in Islamic Banking, in theoretically and the implementation of risk management. The scope of this study will include the identification of risk in Islamic Banking, stage of risk management in Islamic Banking, risk management model, and also the devolpment of risk management framework in Islamic Banking.